Uniwersytet jako źródło traumy: "Wydechy z bezrybocia" Piotra Sobolczyka i "Harcowanie na planie. Her-storia stawania się matką-akademiczką w polskim uniwersytecie" Beaty Karpińskiej-Musiał - Morska, Izabela (Zagadnienia Rodzajów Literackich, 2024)
The article examines the university as a source of trauma through an analysis of two narratives of resistance: Exhales from Unfishployment by Piotr Sobolczyk and Enter stage left. Her-story of Becoming Mother-academic at a Polish University by Beata Karpińska-Musiał. Drawing on Pierre Bourdieu’s depiction of academia as a system of reproduction, the study highlights the punitive mechanisms faced by those who deviate from the neoliberal ideal of homo academicus, characterized by total dedication to institutional demands. Both authors, despite their commitment to academic life, recount public humiliation and professional ostracism for daring to maintain private lives outside the academy, as well as for demonstrating the type of broad education that includes, in addition to integrity and generosity of spirit, mastering multiple languages, engaging with international academic contexts, and maintaining high levels of professional mobility. The article underscores how structural constraints, fueled by neoliberal and ritualistic institutional practices, target individuals based on identity factors such as parenthood, queerness, or disabilities. Creative resistance emerges as a shared theme, manifesting in Sobolczyk’s poetry and Karpińska-Musiał’s autoethnographic prose. These works expose the oppressive ethos of academic labor and advocate for alternative narratives of freedom and resistance, including the queer art of failure, that challenge systemic unfairness. By engaging theorists like Bourdieu, Foucault, MacIntyre, Nussbaum, and Sontag, the article calls for a reimagining of academia as a humane and equitable space. It critiques the inefficiency of traumatizing talented academics, proposing instead a system where work-life balance and professional dignity prevail.